Socioeconomic and behavioural factors that contribute to the co-occurrence of risk factors for noncommunicable diseases - Naftal Sakaria; Nelago Indongo (BMC Public Health)
Abstract It is observed that the global burden of diseases had shifted from infectious diseases to Non-Communicable Diseases (NCDs), with an accumulative trend in developing countries. NCDs share key modifiable behavioral risk factors like unhealthy diet and lack of physical activity that are typically established during adolescence or young adulthood and will set the stage for NCDs development later in life. Therefore, this paper aimed to explore factors contributing to the co-occurrence of risk factors for NCDs among persons aged 30 years and above in selected urban areas of Namibia. Specifically, the paper focused on examining the social, economic and behavior characteristics of people living with NCDs and how they contribute to the relative risk of the co-occurrence of NCDs. The study is based on secondary data and analysis is based on a total sample of 1527 which was successfully interviewed. The dependent variable was co-occurrence of NCD risk factors per respondent with the following groups: No co-occurrence, at most two risk factors, 3–4 risk factors, and 5–6 risk factors. The risk factors included excessive alcohol consumption, smoking of tobacco, insufficient physical activeness, insufficient intake of fruits, and insufficient intake of vegetable and unhealthy dietary pattern. Descriptive statistics were obtained using frequencies and averages. Pearson Chi-square was used to assess the association between co-occurrence of risk factors and socio-economic and behavioural variables using cross-tabulation. A multinomial regression model was also used to predict the effects of factors contributing to the co-occurrence of risk factors. The significance of variables was tested using 5% level. The results showed that overall, co-occurrence of risks was more prevalent among respondents with HBP than those with diabetes or HRD. Notably, age and education level positively contribute to co-occurrence of risk factors of NCDs. Increased co-occurrence of risks was also relatively high among respondents with NCD who did not take medication and those who did not go for follow up. The paper concluded that taking medication, regular check-up and following healthy diet significantly reduce the risk of co-occurrence of NCD risk factors. The study recommends for infrastructural developments in urban areas that promotes health lifestyles including provision for cycling, walking paths and participation in urban agriculture.